GAMBARAN KEPATUHAN BIDAN DALAM PENGISIAN BUKU KIA IBU HAMIL DI WILAYAH IBI RANTING RAMBIPUJI - Puspitawati, Kurnia; M, Syiska Atik; R, Dian Aby (HEALTHY : Jurnal Inovasi Riset Ilmu Kesehatan, 2025)
The KIA Handbook is a source of maternal and fetal health information used by health workers, especially midwives, as a communication medium. This handbook is provided to every pregnant woman up to the age of 6 years. Based on the 2018 East Java Basic Health Research (Riskesdas), 75.5% of mothers have a KIA handbook, while 24.5% do not. Based on a preliminary study, a small percentage (30%) of midwives in the IBI branch of the Rambipuji Community Health Center (Puskesmas) comply with documenting in the KIA handbook. The purpose of this study was to describe midwives' compliance in completing the KIA handbook for pregnant women in the IBI branch of the Rambipuji branch. Method: The research design was descriptive with a descriptive survey method. The population was 52 TPMB and the sample was 52 TPMB using a saturated sampling technique. The instruments used were a questionnaire and the KIA handbook for pregnant women. Some midwives are compliant with documenting their care in the Maternal and Child Health (KIA) book, which consists of five indicators. The compliance rate includes identity (13.5%), maternal care (0%), delivery mandate (5.8%), pregnancy care chart (42.3%), and weight gain chart (15.4%). Midwives in the Rambipuji branch of the Indonesian Midwifery Association (IBI) do not document care in accordance with regulations. This issue should be addressed by the regional IBI to improve midwives' abilities and skills in completing the KIA book by conducting training. ABSTRAKBuku KIA merupakan sumber informasi kesehatan ibu dan janin yang digunakan oleh petugas kesehatan khususnya bidan sebagai media komunikasi.  Buku ini diberikan pada setiap ibu hamil hingga anak berusia 6 tahun. Berdasarkan data Riskesdas Jawa Timur 2018 sebanyak 75,5%  ibu memiliki buku KIA dan 24,5 % ibu tidak memiliki buku KIA. Berdasarkan studi pendahuluan sebagian kecil (30%) bidan di wilayah IBI ranting Puskesmas Rambipuji patuh melakukan pendokumentasian di buku KIA. Tujuan penelitian ini untuk menggambarkan kepatuhan bidan dalam pengisian buku KIA ibu hamil di wilayah IBI Ranting Rambipuji. Desain penelitian deskriptif dengan metode survey deskriptif. Populasi sebanyak 52 TPMB dan sampel 52 TPMB teknik sampling adalah sampel jenuh. Instrumen menggunakan kuesioner dan buku KIA ibu hamil. Sebagian bidan yang patuh dalam melakukan pendokumentasian dibuku KIA yang terdiri dari 5 indikator, angka kepatuhan meliputi identitas (13,5%), pelayanan ibu (0%), amanat persalinan (5,8%), grafik pelayanan kehamilan (42,3%) dan grafik peningkatan berat badan (15,4%) Bidan di wilayah IBI ranting Rambipuji tidak melakukan pendokumentasian asuhan yang  sesuai dengan ketentuan. Hal ini dapat menjadi perhatian oleh IBI wilayah untuk meningkatkan kemampuan dan keterampilan bidan dalam pengisian buku KIA dengan mengadakan pelatihan